Job insecurity and moral disengagement in frontline employees: A moderated mediation effect of perceived organizational support and occupational regret - Prakash Kumar Gautam; Dhruba Kumar Gautam (Intangible Capital)
Purpose: The study's purpose is to analyze the effect of job insecurity on the moral disengagement of frontline employees during the COVID-19 pandemic. It also analyzes the moderated mediation model incorporating occupational regret and perceived organizational support.